Changes in the Dimensions of Life of Filipino Deportees from Malaysia - Bagian Aleyssa A. Abdulkarim (Asian Social Work Journal, 2016)
This research examined the life experiences of Filipinos deported from Malaysia. Anchored on the symbolic interaction theory, the study sought to investigate how the interpretation of these experiences defined and shaped their personhood. It documented the life experiences of Filipino deportees before and after deportation from Malaysia to determine the consequences of such forcible repatriation on their health, socio-economic, cultural and psychosocial dimensions of life. The study looked into coping strategies with life changes focusing on deportation as a main turning point and identified this event’s differential treatment considering the variables of age and sex group. The research utilized a exploratory design and presented extensive case studies of 24 Filipino deportees, eight of which are included in this paper synthesized from in-depth interviews of deportees and key informants. Other technique used were non-participant observation and data gathering from records of government offices assisting the repatriates including the Department of Social Welfare and Development Region 9 and the Zamboanga City Philippines Social Welfare and Development Office. The study showed varying consequences of deportation with respect to the deportees’ health, socio-economic, cultural, and psychosocial condition. While all the respondents admitted having been adversely affected by their deportation there is evidence of remarkable resiliency and optimism as gleaned from their narrations. Deportees have varied interpretations of deportation in their lives. For some respondents, the experience meant re-connection and re-union with the family in the place of origin. For others, the experience meant free travel to their homeland. A number of respondents reported deportation was an opportunity to be free from detention, an experience which they described as